Nutritional Status and Quality of Life in Breast Cancer Patients in Karawaci General Hospital - KURNIAWAN, ANDREE; LUGITO, NATA PRATAMA HARDJO (Indonesian Journal of Cancer, 2016)
ABSTRACTCancer is related to a deterioration of nutritional status and quality of life (Qol), but the extent of these conditions in patients with breast cancer has not been studied well. Malnutrition is prevalent among cancer patients and maybe correlated with altered quality of life. The aim of this study is to evaluate the association of QoL and nutritional status after breast cancer diagnosed. Nutritional status was evaluated with Patient Generated Subjective Global Assessment and QoL using Short form 36 (SF-36) and also with the specific module for breast cancer patients. A consecutive sampleof twenty two patients diagnosed with breast cancer was evaluated. The associations of QoL with stadium and nutrition status were evaluated using T-test analysis. The mean of body mass index was 21.3 kg/m2. Fifty percent patient have menopause. Most patients were stage II (77.3%), the others stage III (18.2%) and stage I (4.5%). Sixty eight point two percent had risk of malnutrition. The stadium of tumor was significantly related to physical functioning (p < 0.000), physical limitation (p < 0.024), emotional limitation (p < 0.013), well-being (p < 0.020), health changes (p < 0.010). Thestatus of nutrition was significantly related to physical functioning (p < 0.001), loss of energy (p < 0.010) and general health (p <0.005). For Conclusion, the status of nutrition breast cancer patients were related to QoL especially physical functioning, loss of energy and general health after they were diagnosed.ABSTRAKKanker sangat terkait dengan perburukan status nutrisi dan kualitas hidup. Namun demikian, belum banyak studi yang yang melaporkan masalah nutrisi dan kulitas hidup pada kanker payudara. Malnutrisi sering ditemukan pada kanker dan mungkin terkait dengan perubahan kulaitas hidup. Tujuan penelitian ini adalah untuk mengevaluasi hubungan antara kualitas hidup dengan status nutrisi setelah kanker payudara terdiagnosis. Evaluasi status nutrisi dilakukan dengan Patient Generated Subjective Global Assessment dan kualitas hidup dengan Short form 36 (SF-36) sertakarakteristik pada kanker payudara. Sampel diambil dengan teknik konsekutif terhadap 22 pasien yang terdiagnosis kanker payudara. Hubungan kualitas hidup dengan stadium kanker dan status nutrisi dinilai menggunakan analisis T-test. Indeks massa tubuh rata-rata adalah 21,3 kg/m2. Lima puluh pasien telah menopause. Terbanyak adalah stadium 2 (77,3%), stadium 3 (18,2%), dan stadium 1 (4,5%). Enam puluh dua koma dua persen berisiko malnutrisi. Stadium tumor secara bermakna berhubungan dengan fungsi fisik (p <0,000), keterbatasan fisik (p<0,024), keterbatasan emosi(p<0,013), rasa nyaman (p<0,020), dan perubahan kesehatan (p<0,000). Status nutrisi berhubungan secara bermakna dengan fungsi fisik (p<0,001), kehilangan energi (p<0,010), dan kesehatan secara umum (p<0,005). Simpulan, status nutrisi pasien kanker payudara berhubungan dengan kualitas hidup, terutama fungsi fisik, kehilangan energi, status kesehatan umum setelah mereka terdiagnosis.